KEBIJAKAN PENGATURAN MUSIK KECIMOL DALAM BUDAYA SASAK NYONGKOLAN DI KECAMATAN JONGGAT TAHUN 2021 (STUDI KASUS DI DESA SUKARARA) - Hidayat, Rahmad; Mustamin, Mustamin; Mintasrihardi, Mintasrihardi; Nazwin, Asfarony Hendra (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
The phenomenon of the Nyongkolan procession with kecimol music has become a trend and even a habit in all areas of the island of Lombok, there was no Jonggat sub-district before. The nature of the people who are less able to filter out foreign culture or new ideas that can damage the original Sasak customs, including considering kecimol music as the original Sasak culture. Seeing the various negative impacts of this, the Jonggat sub-district government in this case Sukarara village made a policy of regulating kecimol music in Nyongkolan and it can be said to be successful. The regulation of the use of kecimol music in the Sasak Nyongkolan cultural series, Sukarara village, Jonggat sub-district is a form of government effort located at the sub-district to village level to restore the authenticity of the Sasak culture in a series of traditional wedding ceremony processions. Nyongkolan should be regulated by mutual agreement between the village heads in the Jonggat sub-district. From this phenomenon, the research team is interested in knowing the function of kecimol music regulation and knowing the challenges related to kecimol music regulation policy. This research is a descriptive type with a qualitative approach. Collecting data by in-depth interviews, observations, and technical documentation. Interactive data model analysis, where data collection until the research ends simultaneously and continuously with interpretation and data reference referring to theoretical references according to research problems. The results showed that Nyongkolan which is a tradition of the people of Lombok, especially in Sukarara Village, Kec. Jonggat Kab. Central Lombok where there is no significant ban on the use of kecimol music because there are no clear regulations. Village and sub-district governments can only encourage the use of traditional musical instruments and do not cross state roads. The Covid-19 moment also influenced the Nyongkolan setting when this research was conducted.